Distribution of 2, 3, 7, 8-substituted polychlorinated dibenzo-p-dioxin and polychlorinated dibenzofurans in the Jukskei and Klip/Vaal catchment areas in South Africa. (February 2016) - Rimayi, Cornelius; Chimuka, Luke; Odusanya, David; de Boer, Jacob; Weiss, Jana
Abstract: Comprehensive two dimensional gas chromatography (GCxGC)-μECD analysis was used to determine 2, 3, 7, 8-substituted dibenzo- p -dioxin (PCDD) and polychlorinated dibenzofuran (PCDF) distribution in the Jukskei and Klip/Vaal catchment areas from ten sites previously identified as persistent organic pollutant hotspots in major rivers in the Gauteng province of South Africa. Five sediment samples from the Jukskei River catchment area and five sediment samples from the Kilp/Vaal River catchment area were collected for analysis. The extracts were screened for dioxin-like activity using the DR-Luc bioassay prior to GCxGC-μECD analysis. All sediment samples tested positive for dioxin-like activity with total activity ranging from 16 to 37 pg toxic equivalents (TEQ) g −1 dry weight (dw) for the Jukskei River catchment and 1.5–22 pg TEQ g −1 dw for the Klip/Vaal River catchment, indicating that the Jukskei River catchment area had higher concentrations of total dioxin-like compounds. Confirmatory tests for the presence of the most potent seven PCDDs and ten PCDFs conducted using GCxGC-μECD revealed presence of 11 PCDD/Fs and 6 PCDD/Fs in the Jukskei and Klip/Vaal River catchments respectively. Total organic carbon (TOC) and particle size distribution analysis were conducted to understand the distribution of PCDD/Fs within the Jukskei and Klip/Vaal catchments. Graphical abstract: Highlights: DR-Luc bioassay screening showed the presence of dioxin-like compounds. GCxGC-μECD analysis confirmed the presence of PCDD/Fs in sediment samples. TOC could not sufficiently describe the trends and distribution of PCDD/Fs. Particle size distribution could not account for of PCDD/F distribution and trends.